Renewal of Intellectual Property Execution Auction Regulations to Support Creative Economy Actors Financing Schemes - Rio, Fildzah; Abubakar, Lastuti; Sugiharti, Dewi Kania (Jurnal Hukum dan Kenotariatan, 2024)
Government Regulation Number 24 of 2022 concerning the Implementation of Law Number 24 of 2019 concerning the Creative Economy aims to optimize intellectual property as credit or financing collateral for creative economy actors. From the banking side, intellectual property as an object of collateral cannot be implemented for various reasons, including those related to the execution of intellectual property in the event of bad credit or financing. Eventhough auction regulations recognize intellectual property as intangible assets that can be executed, they still don’t provide legal certainty for both creditors and debtors. This research aims to analyse regulatory constraints in intellectual property execution auctions and renewal in auction regulations that need to be carried out to support creative economy financing schemes. This research uses a normative juridical approach with analytical descriptive research specifications and qualitative juridical data analysis. Based on the research, the following results were obtained: Although intellectual property is recognized as an object of execution auctions, regulation haven’t provide certainty regarding the execution mechanism, especially regarding the transfer of intellectual property rights. So, the idea is to make the rules stricter so that execution auctions can support intellectual property-based financing schemes for people working in the creative economy.